Cuidado de enfermería en el paciente crítico con traqueostomía percutánea - Hinojosa Taris, Vanessa Yolanda (2025)
Percutaneous tracheostomy is a medical procedure performed to establish a safe airway in patients with respiratory problems, being less invasive than traditional surgical tracheotomy and must be performed by trained medical personnel and since it can have associated risks such as bleeding, infection or damage to nearby structures, so this study was proposed to describe nursing care in the critical patient with percutaneous tracheostomy, using a qualitative approach, supported by the bibliographic review with a descriptive scope, highlighting among the main results that the adequate maintenance of the tracheal cannula as well as the prevention of infections are the key pillars within nursing practice in nursing care in critical patients with percutaneous tracheostomy, so it has been determined that the rigorous monitoring of signs of complications such as the displacement of the tube or airway instruction allows to avoid adverse events that may compromise the patient's life, in the same way the application of secretion aspiration techniques with asepsis measures has been shown to be an intervention that reduces the incidence of respiratory infections, concluding that the training of nursing staff in the care of these patients reduces the Technical errors during the management of this procedure reinforcing the importance of establishing standardized protocols in intensive care units since the use of clinical guidelines and procedures improve the quality of care and reduce the variability of clinical practice.